Implementation of local proprietary symmetric and asymmetric algorithm as secure plug-in on microsoft outlook / Mohd Izhar Jaafar - Jaafar, Mohd Izhar (2012)
Email is the most important communications system in the world. However the internet traffic between the sender and recipient is routed through many countries, even they live on the same area and the content of email messages are generally not encrypted and unsecured. They need to communicate in secure environment to avoid eavesdropping or interception. The purpose of this study was to design and develop new secure plug-in on Microsoft Outlook using integration of symmetric and asymmetric cryptographic algorithm. The design was combined with two types of cryptographic algorithm to have an extra level of security value. It have increase complexity of process encryption and decryption. New integration also have an extra value security because of the symmetric algorithm was developed locally in Malaysia. Apart from symmetric algorithm, Public Key Infrastructure technologies that one of the asymmetric algorithm have been select as a part of new integration. It have been utilized the Public and Private Key to have an extra level for user authentication. Security analysis was performed to verify the new secure plug-in in encrypted format during transmission over the network. It was conducted to intercept transmission between the sender and recipient. The findings show that the new integration has capabilities to send encrypted messages during transmission process and give the secure communication channel especially for secure email system. For future research, the new integration can be proposed to integrate with digital signature to avoid interception.